Skin‐Compatible Carbopol Electrospun Fiber Membranes with pH‐Dependent Rheological Properties for Biomedical Applications - Daewoo Han; Robert Horvath; Burcu Uner; Giovanni M. Pauletti; Andrew J. Steckl (Macromolecular Materials and Engineering, 2025)
Abstract Properties of pH‐responsive electrospun nanofibers incorporated with biocompatible/degradable Carbopol, commonly used in pharmaceuticals and personal care products, are reported. Sonication of Carbopol dispersions prior to electrospinning leads to uniform incorporation into fibers of the host polymer polyvinylpyrrolidone. The hydration behavior is strongly influenced by pH conditions, forming a viscous network at higher pH. Since Carbopol is more responsive to higher pH, at pH > 6 increasing Carbopol concentration leads to increased uptake volume of buffer solution, faster uptake rate and complete gel formation. The physical spreadability (resulting from a combination of viscoelastic properties and the structural polymer network) of the hydrated fibers is evaluated for multiple Carbopol concentrations and pH conditions. At low starting pH of 4, increasing the Carbopol amount results in slightly increasing viscosity while maintain solution pH. On the other hand, at high starting pH of 8 increasing Carbopol concentrations result in significant reduction in the pH of the buffer solution, which in turn decreases the viscosity of the gel and increases its spreadability. These findings provide guidelines for rational designs of pH responsive Carbopol fibers for various applications, including drug delivery, wound dressing, contraceptive devices, and prevention of sexually transmitted diseases.